Development of a point-of-care device for syphilis infection screening - Tan, Brandon Peng Wai. (2013)
The ability of conduct self-testing of diseases from a single drop of blood in a point-of-care setting has been of great interest by many researchers. While the application of lateral flow technology to screen for pregnancy has been a great success story, many of the blood-based or serum-based lateral flow tests are limited to be used in clinic settings. Poor sensitivity in the inherent lateral flow technology leads to a requirement for large amounts of blood (> 50 l) required during testing, making it difficult for an untrained person to conduct the test. Alternative approach using microfluidic techniques appear promising to miniaturize immunoassays with improved sensitivity. However, the requirements of pumps in microfluidic device to drive fluids and specialized readers for interpretation make microfluidic platform less attractive for commercial use. Hence, advancements in immunoassay technology are necessary to path ways for novel easy-to-use home-based test kits.